Remediation of heavy metal-contaminated paddy soils using biochar and its effect on corn growth and yield - Mayadewi, Ni Nyoman Ari; Rai, I Nyoman; Indrayuni, Dewa Ayu Bulan (Brawijaya University, 2025)
Badung River, a primary irrigation source for the subak system in South Denpasar, has been reported to contain excessive levels of heavy metals, exceeding the standard quality for irrigation water. Corn cultivated on subak systems irrigated by this irrigation source had heavy metal residues in its roots and kernels. Long-term consumption of corn containing heavy metals such as Pb, Cd, Cu, Cr, and Hg will cause toxicity to plant tissues and the human body. This study examined the content of heavy metals in soil and corn plants in subak systems in South Denpasar, which are irrigated with water from the Badung River. Remediation of the soils contaminated by heavy metals was conducted using rice straw and husk biochar (Br), coconut coir and shell biochar (Bc), vegetable and fruit waste biochar (Bw), and lignohumic biochar (Bl). The study also evaluated the effect of applying biochar on growth and yield of corn grown on soils contaminated by heavy metals. The results of this study showed that the heavy metal contents in the soil and irrigation exceeded the threshold for soil and water quality standards. The application of Bl yielded the highest biomass fresh weight and seed weight at 14% moisture content compared to other treatments. The Bl treatment also resulted in the best performance in binding and translocating heavy metals based on the bioaccumulation and translocation values ??of the biochar types. Hence, it can be concluded that the most suitable biochar for the remediation of heavy metal-contaminated paddy soils in subak systems is lignohumic biochar.